Pertumbuhan Tanaman Padi Fase Vegetatif Dan Akumulasi Logam Berat Pada Jaringan Tanaman Padi Varietas Payo Besar dan Inpari 12 Di Lahan Gambut Yang Diberi Amelioran Dregs - Nia Surani Silaban; Nelvia '; Idwar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
ABSTRACT The aims of the research were to study the effect of the application of ameliorant dregs in peatlands on the growth of rice and Pb, Ni, Cr and Se contents of shoot rice. The research was conducted on peatlands in Tanjung Air Hitam village, Kerumutan district, Pelalawan-Riau, from Agust 2012 to April 2013. The experiment used Split Plot Design and three replications, varieties of rice (Payo Besar and Inpari 12) as main plot and ameliorant of dregs consisted of: 1,25; 2,5 and 5 ton per hectare as the sub plot. The result of research showed the application of dregs 1,25 ton per hectare increased the plant height, maximum tiller number and weight of dry shoot. The Pb and Ni of shoot rice were very low and Cr and Se were not measurable. Keywords : Peatland, Dregs, Rice, Heavy Metals.